The house on Fripp Island - Kauffman, Rebecca (Houghton Mifflin Harcourt, 2020)
"A taut, page-turning novel of secrets and strife: When two families-one rich, one not-vacation together off the coast of South Carolina, little do they know that someone won't be returning home"--